Active Nerve Regeneration with Failed Target Reinnervation Drives Persistent Neuropathic Pain - Xie, Wenrui (eNeuro, 2017)
Peripheral nerves can regenerate and, when injured, may cause neuropathic pain. We propose that the active regeneration process plays a pivotal role in the maintenance of neuropathic pain. In one commonly used rodent neuropathic pain model, pronounced pain behaviors follow ligation and cutting of the L5 spinal nerve. We found that the injured nerve regenerates into the sciatic nerve and functionally reinnervates target tissues: the regenerated nerve conducts electrical signals, mechanical responses, and tracers between the leg/hindpaw and axotomized sensory ganglion. The regenerating nerve is the primary source of abnormal spontaneous activity detected in vivo. Disrupting the regeneration inhibited pain. First, semaphorin 3A, an inhibitory axonal guidance molecule, reduced functional regeneration, spontaneous activity, and pain behaviors when applied to the injury site in vivo. Second, knockdown of the upregulated growth-associated protein 43 (GAP43) with siRNA injected into the axotomized sensory ganglion reduced pain behaviors. We next examined the spared nerve injury model, in which pain behaviors are essentially permanent. The regeneration resulted in tangled GAP43-positive neuromas at the nerve injury site without target reinnervation. Perfusing the nerve stump with semaphorin 3A, but not removing the tangled fibers, prevented or reversed pain behaviors. This effect far outlasted the semaphorin 3A perfusion. Hence, in this model the long-lasting chronic pain may reflect the anatomical inability of regenerating nerves to successfully reinnervate target tissues, resulting in an ongoing futile regeneration process. We propose that specifically targeting the regeneration process may provide effective long-lasting pain relief in patients when functional reinnervation becomes impossible.